A Study to Assess Morbidity Patterns among the Solid Waste Workers in Municipal Corporation of a Metropolitan City (GAIMS Journal of Medical Sciences, 2023)
Background: The International Labour Organization (ILO) has projected that over 125 million workers face occupational accidents and illnesses within a single year, leading to roughly 220,000 fatalities and impacting about 10 million individuals who suffer significant disabilities. This alarming scenario is compounded by the fact that municipal workers handling solid waste, often hindered by limited education, knowledge, and awareness, find themselves at an elevated vulnerability to occupational hazards. Their line of work exposes them to a diverse range of risk factors including dust, bio-aerosols, volatile organic compounds, and mechanical strain, all of which contribute to their heightened susceptibility to various occupational diseases. This study was conducted to assess the morbidity pattern among the solid waste workers and to study epidemiological correlates affecting health of solid waste workers.Material and methods: Study Area was ‘M’ ward of the metropolitan city Mumbai. Study was carried out from June 2012 to July 2013. 160 Permanent male workers who were handling the solid waste and who agreed to participate were included in the study. Employees were contacted at their work place. According to their convenient timing interviews were taken & examination was carried out.Results: Out of 160 employees, 49.4% employees were in 20-29 year age group and 11.9% employees were above 40 years age group. Most of the employees were belonging to Lower Upper Class (IV). Out of 160 participants, 58 were obese and hypertension was found in 37 participants.Conclusion: The study unveils a comprehensive overview of the morbidities prevalent among municipal waste workers, highlighting the diverse range of health challenges they encounter in their daily activities.